Impact of Learning Capability on Organizational Performance in the Nepalese Banking Sector - Manandhar, Raju Bhai (Management Dynamics, 2021)
The Nepalese banking sector must retain and attract qualified human resources to achieve its goals. Job satisfaction is crucial for the retention and attraction of competent people in the organization. The learning capability has been considered a vital index of an organization’s effectiveness to innovate and grow (Jerez-Gómez et al., 2005). The purpose of the study was to examine the association and impact of learning capability on organizational performance in Nepalese commercial banks. The present study is descriptive and analytical in nature. The questionnaire survey method was adopted with a five-point Likert scale. This survey has conducted in Kathmandu Valley, focusing on employees of public and private banks such as managers, accountants, cashiers, and assistant level workers in the respective department respondents. Fifty respondents were chosen from four public and private banks. To choose the respondents for the study, the judgmental sampling technique was applied. In this research, correlation and regression analysis has been carried out to assess an association and the impact of learning capability on organizational performance. The study found a positive association between learning capability and organizational performance. It also found an effect of learning capability on organizational performance in Nepalese commercial banks. It is also found that gender has no impact on learning capability and organizational performance in the Nepalese banking sector.